THE EFFECT OF RELIGIOSITY AND SOCIAL SUPPORT ON MARRIAGE READINESS IN THE YOUNG ADULT AGE GROUP - Ramdani, Nur Syifa; Herawati, Tin; Musthofa (Journal of Child, Family, and Consumer Studies, 2023)
Indonesia has experienced a decline in marriage rates in the last ten years. Religiosity and social support have an important role in preparing individuals for marriage. This study aims to analyze the influence of young adult characteristics, family characteristics, religiosity, social support, on marital readiness in the young adult age group. The research design used was a cross-sectional study with a quantitative approach. This study involved unmarried young adults aged 21 to 30 years. Respondents in this study totaled 60. The research location was in the Central Bogor Sub-district, Bogor City, West Java. Nonprobability sampling was conducted using purposive sampling technique. The results of the t test obtained a significant difference between the religiosity of men and women. The correlation test shows that there is a significant positive relationship between respondents' age, number of families, religiosity, social support and marital readiness. The regression test results show that income, number of family members, and religiosity have a significant positive effect on marital readines.